Titanium implant with nanostructured zirconia surface promotes maturation of peri-implant bone in osseointegration. (May 2013) - Dusad, Anand; Chakkalakal, Dennis A; Namavar, Fereydoon; Haider, Hani; Hanisch, Brock; Duryee, Michael J; Diaz, April; Rensch, Adam; Zhang, Yijia; Hess, Ryan; Thiele, Geoffrey M; Fehringer, Edward V
The goal of the experiment outlined in this article is to improve upon noncemented methods of arthroplasty for clinical application in elderly patients. This was done by determining whether titanium implants with a novel nanostructured zirconia surface, which was created by ion beam–assisted deposition, would prevent impaired osseointegration of intramedullary implants in 1-year-old rats receiving a protein-deficient diet. Specifically, we asked whether the implant with the nanostructured zirconia surface would increase expression of markers of bone maturation within the remodeling of peri-implant woven bone. The control implants, which were made of commercially pure titanium, had a polished surface ex vivo but are known to acquire a microstructured titania surface in vivo. Ten 1-year-old rats received experimental implant (group A) and 10 had control (group B) implants. Ten 3-month-old rats received normal protein diet and the control implant (group C). Animals were euthanized 8 weeks after implantation, and transverse sections of femur-implant samples were used for histology, micro-computed tomography and immunohistochemical evaluations. In group B, the expression of α2β1 and α5β1 integrins, which are known to mediate osteoblast adhesion, glycosaminoglycans, heparan sulfate and chondroitin sulfate, was less than half of that in group C. Important to this study, the zirconia surface used in group A prevented these deficiencies. Therefore, these results indicate that nanostructured zirconia surface created on clinical implants by ion beam–assisted deposition may prevent impaired osseointegration in elderly patients by promoting quicker maturation of peri-implant woven bone.